2003
DOI: 10.1002/mrc.1230
|View full text |Cite
|
Sign up to set email alerts
|

Conformational study of fosinopril sodium in solution using NMR and molecular modeling

Abstract: Two conformers of fosinopril sodium in methanol were unambiguously established using 2D NMR methods and variable-temperature NMR experiments. Differences in their conformational structure were shown to be related to the rotational energy barrier about the amide bond and hydrophobic interaction. The relationship between the 3D structure and activity is discussed. It is suggested that the trans-conformer may be more biologically active owing to its stacking structure and strong hydrophobic interaction and the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Although its conformation cannot be perfectly accounted for neither by the NMR data, which 'sees' an average conformation, nor by the conformational analysis, which omits some thermodynamic factors, the small distance deviations indicate that the model represents faithfully the most stable conformation of A1 in solution. The distances of 4.64 and 4.45 found by molecular modeling between protons Ph(o) and Ha¢, and between protons A and E, respectively, are too large to generate visible correlation peaks in the ROESY spectra and are in agreement with the absence of correlation peaks for these protons (13). Taken together, the above results confirm that compound R207910 (A1) belongs to the (RS, SR) couple of diastereoisomers as suggested by the qualitative spectra analysis.…”
Section: Analysis Of R207910 By a Combined Nmr And Molecular Modelingsupporting
confidence: 64%
See 2 more Smart Citations
“…Although its conformation cannot be perfectly accounted for neither by the NMR data, which 'sees' an average conformation, nor by the conformational analysis, which omits some thermodynamic factors, the small distance deviations indicate that the model represents faithfully the most stable conformation of A1 in solution. The distances of 4.64 and 4.45 found by molecular modeling between protons Ph(o) and Ha¢, and between protons A and E, respectively, are too large to generate visible correlation peaks in the ROESY spectra and are in agreement with the absence of correlation peaks for these protons (13). Taken together, the above results confirm that compound R207910 (A1) belongs to the (RS, SR) couple of diastereoisomers as suggested by the qualitative spectra analysis.…”
Section: Analysis Of R207910 By a Combined Nmr And Molecular Modelingsupporting
confidence: 64%
“…The present study refers to experiments made in CDCl 3 , the solvent that showed a better signal separation. All NMR experiments were carried out by using a Bruker Avance DRX 400 spectrometer (Bruker, Wissembourg, France) equipped with a reverse double-resonance ( 1 H, 13 C, SEI) probe head with z-gradients and operating at 400 MHz for proton and 100 MHz for carbon. The 1D and 2D NMR spectra were obtained at temperature of 298 K. The complete assignment of all protons and carbons was underwent by 2D experiments: COSY ( 1 H-1 H; 9), HMQC ( 1 H, 13 C; 10), and HMBC ( 1 H, 13 C; 11), all performed with gradients into Icon-NMR and with automatic calculation of spectral width.…”
Section: Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…The quaternary carbon atoms were identified by HMBC. The assignments of 1 H-and 13 C-NMR resonances in the two solutions are listed in Table 1. …”
Section: Nmr Assignmentsmentioning
confidence: 99%
“…All NMR experiments were performed at 300K on a BRUKER AV400 spectrometer equipped with a 5 mm gradient inverse broadband probe. MD simulations [13][14][15][16][17] were carried out by weak coupling in a temperature bath with a relaxation time of 100fs. No cutoff distance was used for all possible interactions.…”
Section: Generalmentioning
confidence: 99%